2016
DOI: 10.1016/j.bandl.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Predictive coding of phonological rules in auditory cortex: A mismatch negativity study

Abstract: The brain is constantly generating predictions of future sensory input to enable efficient adaptation. In the auditory domain, this applies also to the processing of speech. Here we aimed to determine whether the brain predicts the following segments of speech input on the basis of language-specific phonological rules that concern non-adjacent phonemes. Auditory event-related potentials (ERP) were recorded in a mismatch negativity (MMN) paradigm, where the Finnish vowel harmony, determined by the first syllabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Note that the major source of co-articulation, the consonant /k:/, was the same for all stimuli. Acoustical measurements conducted in a previous study (Ylinen et al, 2016) suggested that in similar bisyllabic Finnish stimuli, first-syllable vowels had a minimal co-articulatory effect on following vowels, not exceeding just noticeable difference.…”
Section: Procedures and Data Analysismentioning
confidence: 83%
See 1 more Smart Citation
“…Note that the major source of co-articulation, the consonant /k:/, was the same for all stimuli. Acoustical measurements conducted in a previous study (Ylinen et al, 2016) suggested that in similar bisyllabic Finnish stimuli, first-syllable vowels had a minimal co-articulatory effect on following vowels, not exceeding just noticeable difference.…”
Section: Procedures and Data Analysismentioning
confidence: 83%
“…In both conditions, the standard syllable was expected to create sequence-level predictions of hearing this particular syllable ( Figure 1C and D, longer arrows). In the Context condition, however, the context syllable representing a familiar word beginning was expected to create predictions at another level, namely, to create word-level predictions of hearing the ending of some familiar word ( Figure 1D, shorter arrows; for discussion on knowledgebased predictions, see Poeppel & Monahan, 2011; for phonological predictions in pseudowords, see Ylinen, Huuskonen, Mikkola, Saure, Sinkkonen et al, 2016). To probe the predictions at sequence and word levels, we presented two deviant syllables ( Figure 1A and B).…”
Section: Introductionmentioning
confidence: 99%
“…Winkler et al, 2009; Garrido et al, 2009) and, as such, the mmn has had a substantial contribution in investigations of underspecification of phonemic representations (e.g. Eulitz & Lahiri, 2004; Näätänen et al, 2007; Winkler et al, 2009; Deguchi et al, 2010; Ylinen et al, 2016; Scharinger et al, 2016, 2017), as well as the phonological representation of stress patterns (e.g. Ylinen et al, 2009; Honbolygó et al, 2004; Honbolygó & Csépe, 2013; Aguilera et al, 2014; Honbolygó et al, 2017; Garami et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Stable environments allow for the development of a robust predictive model, which simultaneously enables an efficient encoding of sensory stimuli while minimizing the demand on cognitive resources 10 . In these environments, healthy individuals form strong predictions about forthcoming sensory stimuli, and their brains consequently produce large prediction error (PE) responses to events that violate such predictions [11][12][13] . The PE response is commonly gauged using electroencephalography (EEG) and an auditory oddball paradigm 14 , in which surprising sounds are embedded in a sequence of predictable sounds.…”
Section: Introductionmentioning
confidence: 99%